Effect of tiotropium on night-time awakening and daily rescue medication use in patients with COPD. Issue 1 (December 2016) - Calverley, Peter; Rennard, Stephen; Clerisme-Beaty, Emmanuelle; Metzdorf, Norbert; Zubek, Valentina; ZuWallack, Richard
Abstract Background Several small studies found night-time awakenings due to COPD symptoms were associated with decreased health status. In this study, night-time awakenings in patients with COPD were examined and effects of tiotropium therapy evaluated. Methods This study was a post hoc, exploratory, pooled analysis of twin, multicenter, double-blind, randomized, placebo-controlled, parallel-group trials. Patients with stable moderate-to-severe COPD were randomized to tiotropium HandiHaler® (n  = 550) or placebo (n  = 371) and followed for 13 weeks. During a 2-week, pre-treatment baseline period and for 13 weeks on treatment, self-reported night-time awakenings due to COPD symptoms, rescue medication (albuterol) use, and morning and evening peak expiratory flow rate (PEFR) were recorded daily. Nightly, COPD-related awakenings were scored: 0 = no awakenings; 1 = 1 awakening; 2 = 2–3 awakenings; or 3 = awake most of the night. Health-related quality-of-life (HRQoL) and energy–fatigue questionnaires were completed at baseline and during treatment. Results Patients were aged 65.2 ± 8.7 years (mean ± SD), with a mean pre-bronchodilator FEV1 of 36.1 ± 13.5 % predicted normal at baseline. Data for night-time awakenings and albuterol use were available for 543 (99 %) patients on tiotropium and 352 (95 %) on placebo. At baseline, 280 (51.5 %) patients on tiotropium and 179 (50.1 %) on placebo reported ≥1 COPD-related night-time awakening per week. Over the 13-weeks' treatment, tiotropium was associated with fewer night-time awakenings, with mean ± SE overall awakening scores per week of 0.356 ± 0.006 compared with 0.421 ± 0.007 for placebo (p  < 0.001); means were significantly lower for tiotropium versus placebo in patients with baseline awakenings (p  < 0.001), but not for those without baseline awakenings. COPD-related night-time awakenings were associated with increased nocturnal rescue medication use and lower HRQoL ratings in both treatment arms. Following start of treatment, tiotropium decreased patients' use of rescue medication compared with placebo, and morning and evening adjusted means for PEFR were higher for tiotropium compared with placebo. Conclusions Tiotropium is associated with decreased COPD-related night-time awakenings. Night-time awakenings are associated with increased nocturnal rescue medication use and may be a surrogate marker of symptom control in patients with COPD.